Impact of fashion entrepreneurship programme on entrepreneurial interests, intention and competencies - Jamaluddin, Rahimah; Ali, Mass Hareeza; Abdul Kadir, Suhaida; Kamis, Arasinah (Universiti Tun Hussein Onn Malaysia, 2019)
Entrepreneurship education has traditionally focused on formal education, but many initiatives have been taken parallel with the 21st century teaching and learning strategies to engage student experience through learning by doing. The purpose of this study was to examine the impact of entrepreneurship education on students’ entrepreneurship interest, intentions and competencies by implementing fashion entrepreneurship program. This study was held at Universiti Putra Malaysia for a period of five months. Samples were selected among undergraduate students who enrolled in Entrepreneurship Courses in First Semester 2016/2017. Screening process comprises interviews and basic sewing test were conducted to select 40 students as the respondents of the program. This program emphasized mentor-mentees system which involved 10 fashion entrepreneurs from the community. Respondents were exposed to entrepreneurship seminars, business and skills trainings, e-marketing workshops, sewing classes as well as evaluation sessions. Qualitative data were gathered through questionnaires adapted from Mc Clellandand Mc Ber & Co (1985) as well as questionnaires by Hisyamudin Hassan (2007). Meanwhile qualitative data were collected through continuous observations and the output of the fashion products. The findings indicated that there is a significant positive correlation between entrepreneurship interests with entrepreneurship intentions. Although the findings showed no significant relationship between fashion entrepreneurship program with entrepreneurship intentions and competencies, respondents’ perceptions towards their interest, intentions and competencies at the end of the program are high. Due to time constraints, it was suggested that future entrepreneurship program should be scheduled more structured and in a timely manner to ensure that student can gain benefit throughout the program and the objective of the program can be achieved.